Customer Participation in the Support System for Small Grocery Retailers - Dawson, John; Terashima, Kazuo (Management School and Economics. The University of Edinburgh, 2004)
In the previous research (Terashima and Dawson, 2004), we discussed a support system for small grocery retailers in order to regenerate them. The purpose of this paper is to show a mechanism which increases customer value of the support system by focusing on customer participation, because increasing customer value has a high priority as the next step for the system. In this paper, we first show that customer participation can be related to customer value through service quality. Then, we review the literature on customer participation in service and retail fields, and make clear the features and problems. After the review, we make clear the significance of a trial of AKR in which the delegates of consumer groups take part in assessing and choosing the buying items. Depending upon the example, we propose a new idea on the role of customer in service provision which is “customer as managerial staff” in the background system, and we also introduce a new idea “indirect participation” about customer participation. At the same time, we consider the importance of the cooperation with other organizations like consumer groups and the forming of good images. Finally, based on these considerations, we propose a wider framework to maximize the effect produced from customer participation. We conclude this paper with contributions to management and research.
Keywords: Economics